2013
DOI: 10.1080/10942912.2011.551864
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer Properties of Pears for Different Drying Methods

Abstract: In the present work, the mass transfer properties of pears were determined for three different drying systems (a solar stove, a direct solar drier, and a drying tunnel), using three calculation methodologies. The results obtained allowed concluding that the best methodology to calculate the mass transfer properties is based on Fick's equation, including shrinkage. The values of the diffusion coefficients in the solar drier and drying tunnel were similar, whereas in the solar stove the diffusivity was lower, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
7
14
0
2
Order By: Relevance
“…ANOVA showed significant differences (P < 0.05) in Bi values caused by different pretreatments applied before drying. The values of the Bi obtained in this study were of the same magnitude of that reported by several authors, from 0.100 to 0.108 for the drying of mango slices (Corzo et al, 2008), 0.1020 to 0.2026 for the drying of pears (Guiné et al, 2013), 0.2060 to 0.3228 during convective drying of broccoli (Mrkic et al, 2007). (Giovanelli et al, 2002;Gely and Santalla, 2007 (Dincer and Hussain, 2002).…”
Section: Resultssupporting
confidence: 74%
“…ANOVA showed significant differences (P < 0.05) in Bi values caused by different pretreatments applied before drying. The values of the Bi obtained in this study were of the same magnitude of that reported by several authors, from 0.100 to 0.108 for the drying of mango slices (Corzo et al, 2008), 0.1020 to 0.2026 for the drying of pears (Guiné et al, 2013), 0.2060 to 0.3228 during convective drying of broccoli (Mrkic et al, 2007). (Giovanelli et al, 2002;Gely and Santalla, 2007 (Dincer and Hussain, 2002).…”
Section: Resultssupporting
confidence: 74%
“…Aside from the focus on equilibrium conditions, interest has grown in describing the diffusivity of moisture. A number of studies have determined the moisture diffusivity of foodstuffs, such as greenbean, black tea, garlic slice and pears, by using a diffusive model based on Fick's second law [9][10][11][12]. The model considers only the internal resistance to moisture immigration.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…With a lumped parameter model concept, all the different types of diffusion are combined in one parameter named as effective moisture diffusivity (D eff ). To obtain the values of D eff , a diffusion model derived from Fick's second law was used[9][10][11][12]. It is noteworthy that the moisture contents used in the diffusion model were in dry basis.The moisture ratio (MR)[10] is an important parameter involved in the diffusion model, which represents the unaccomplished moisture content under certain condition.…”
mentioning
confidence: 99%
“…Nem içeriği ile boyutsuz çaptaki değişim (Dimensionless diameter vs moisture ratio ) 8,56 × 10 −11 -2,25 × 10 −10 m 2 /s aralığında olduğu D eff 'in değerlerinin artan sıcaklıkla arttığı bulunmuştur [23]. Şeker Çözeltileri ile ozmotik dehidrasyona tabi tutularak kurutulan armutlar incelendiğinde; konvektif tepsili kurutucuda doğal kurutulan armutların difüzyon katsayılarının 1,59×10 −10 -7,64×10 −10 m 2 /s, ozmotik dehidre ön işlemi ile muamele edilen armutların difüzyon katsayılarının 1,87×10 −10 -8,12×10 −10 m 2 /s aralığında olduğu [25], taze ve 50 Brixlik sakaroz çözeltisinde farklı süreler bekleterek osmotik dehidrasyona uğratılan armutların 45-65 o C hava sıcaklıkları ve 2,2 m/s hava hızında kurutulması sırasında difüzyon katsayıları 6,5 × 10 −12 -5,8 × 10 −10 m 2 /s aralığında olduğu bulunmuştur.…”
Section: Difüzyon Katsayısı Ve Aktivasyon Enerjisi (Diffusion Coefficunclassified
“…Armut kurutma ve kuruma davranışlarının işlem özellikleri ile ilgili bazı çalışmalar yayınlanmıştır. Farklı armut türleri için [19], armut dilimleri için [20][21][22], osmotik-dehidrasyon ön işlemi uyguladıktan sonra [23,24], sitrik asit ile muamele ederek [21], kuruma sırasında meydana gelen büzülmeyi dikkate alarak [25,26] kurutma yapıldığı gibi, güneş enerjili kurutucularda kurutma [25], laboratuvar tipi konvekif kurutucularda kurutma [20,21] ve kesikli kurutma tekniği kullanılması [27] gibi farklı çalışmalar literatürde mevcuttur. Bu çalışmaların bazılarında kuruma sürecini açıklayan tek tabaka kuruma modelleri de tanımlanmışlardır [28].…”
Section: Gi̇ri̇ş (Introduction)unclassified